Registro da penhora: obrigatoriedade - Habith , Paulo (2018)
Submitted by rsmoira@stj.jus.br (rsmoira@stj.jus.br) on 2018-10-11T17:40:30Z No. of bitstreams: 2 registro_penhora_obrigatoriedade_Habith.pdf: 929366 bytes, checksum: 7db8b5beb8c494fbcaf7228c2a6860b9 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)